Analisis PS dalam Membantu Self-Regulation Pada Pemecahan Masalah Matematika Mahasiswa Prodi Informatika - Ramdhani, Lisda; Ramli, Ramli; Rahmawan, Ardi; Muslimin, Muslimin (Jurnal Ilmiah Mandala Education (JIME), 2021)
The purpose of this study was to describe and explore private speech in helping students self-regulation in solving mathematics problems for students of the Informatics Education Study Program. The approach used in this research is a qualitative approach, with the type of descriptive research. The research subjects were 12 students from 50 Informatics education students. The instruments used are description tests, interviews, questionnaires and observations as well as audio-visual recordings. Data analysis techniques were carried out in three ways, namely, data reduction, data presentation and drawing conclusions. There are three stages in this research, namely the preparation, implementation and report stages. The results of the research in the form of interviews and observations in general are obtained that private speech in its role is very helpful for self-regation, where private speech plays an important role in controlling student attitudes, and increasing academic values and student concentration. Various self-regation experienced by students but it does not become a negative influence on the behavior and daily life of students. Self-regulation experienced by students is controlling student attitudes and behavior when using private speech. Students always do assignments responsibly and on time using private speech, as many as 25% of students choose strongly agree, 58% choose agree and 17% choose less agree. The use of private speech makes students lazy to study, as many as 33% of students chose not to agree and 67% of students did not agree. Good self-regation makes students focus on solving problems, as many as 92% of students choose strongly agree and 8% of students choose agree. Academic value increased by using private speech with good self-regulation, as many as 17% of students strongly agreed and 58% of students agreed and 25% of students did not agree. Private speech is done when they find it difficult to solve problems, as much as 25% choose strongly agree, 42% agree and 33% disagree. Self-regation affects academic scores as much as 33% choose strongly agree, 42% agree and 25% disagree